2013
DOI: 10.1080/00207594.2012.691975
|View full text |Cite
|
Sign up to set email alerts
|

Child physical abuse and neglect in Kenya, Zambia and the Netherlands: A cross‐cultural comparison of prevalence, psychopathological sequelae and mediation by PTSS

Abstract: This study compared the prevalence of self-reported childhood physical abuse and neglect and the associated psychopathological sequelae among Kenyan, Zambian, and Dutch university students. In addition, we sought to find out the differentiated role of posttraumatic stress symptoms (PTSS) in mediating the associations between childhood maltreatment experiences and psychopathology symptoms. The sample consisted of 862 university students from Kenya (n = 375), Zambia (n = 182), and The Netherlands (n = 305) who c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 49 publications
2
40
0
Order By: Relevance
“…There is limited literature examining the mechanisms of transmission of risk for psychopathology from mothers who have experienced ACEs to her child, and this is especially true in low‐ and middle‐income countries (LMIC); however, the exploration of factors mediating this pathway is broadening. ACEs have been shown to have a deleterious impact on later life outcomes that include mental and physical health, educational and financial attainment, and functioning within interpersonal relationships (Barcellos, Carvalho, & Turley, ; Benjet, ; Kessler et al, ; Mbagaya, Oburu, & Bakermans‐Kranenburg, ; Norman et al, ). The relationship between mother and child is particularly vulnerable to such adversity, with consequences that include disrupted parenting, impaired attachment and poor educational and mental health outcomes in children (Lang, Gartstein, Rodgers, & Lebeck, ; Min, Singer, Minnes, Kim, & Short, ; Pereira et al, ; Plant, Barker, Waters, Pawlby, & Pariante, ; Rijlaarsdam et al, ; Schreier et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…There is limited literature examining the mechanisms of transmission of risk for psychopathology from mothers who have experienced ACEs to her child, and this is especially true in low‐ and middle‐income countries (LMIC); however, the exploration of factors mediating this pathway is broadening. ACEs have been shown to have a deleterious impact on later life outcomes that include mental and physical health, educational and financial attainment, and functioning within interpersonal relationships (Barcellos, Carvalho, & Turley, ; Benjet, ; Kessler et al, ; Mbagaya, Oburu, & Bakermans‐Kranenburg, ; Norman et al, ). The relationship between mother and child is particularly vulnerable to such adversity, with consequences that include disrupted parenting, impaired attachment and poor educational and mental health outcomes in children (Lang, Gartstein, Rodgers, & Lebeck, ; Min, Singer, Minnes, Kim, & Short, ; Pereira et al, ; Plant, Barker, Waters, Pawlby, & Pariante, ; Rijlaarsdam et al, ; Schreier et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study conducted in African and Western countries revealed a significantly higher proportion of children being abused and neglected in African countries [7]. Owing to the lack of information on child abuse and neglect in the developing world, Skeen and Tomlinson emphasized on the importance of systematically collecting information on child maltreatment [8].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent meta-analysis, the global prevalence of child maltreatment was estimated at 22.6% (Stoltenborgh, Bakermans-Kranenburg et al 2013); the prevalence varied significantly between countries. One study compared reported rates of abuse and neglect in Kenya, Zambia, and the Netherlands and found that abuse rates were much higher in the African samples, but rates of neglect were similar (Mbagaya, Oburu et al 2013). …”
Section: Introductionmentioning
confidence: 99%